Comparative Effectiveness of Endorphin Massage and Kinesio Taping in Reducing Lower Back Pain Among Third Trimester Pregnant Women at Rowosari Health Center - Elisa Elisa; Dantita Permata (International Forum of Researchers and Lecturers, 2026)
Pregnancy related to low back pain is one of the most common musculoskeletal complaints during the third trimester, primarily caused by hormonal changes, increased body weight, and postural adaptations. Various non-pharmacological interventions have been recommended to manage this condition; few studies have directly compared the effectiveness of Endorphin Massage and Kinesio Taping, resulting in limited comparative evidence to guide evidence-based clinical decision-making. Therefore, this study aimed to compare the effectiveness of Endorphin Massage and Kinesio Taping in reducing low back pain intensity among third-trimester pregnant women. A quasi-experimental study with a pretest–posttest control group design was conducted involving 40 third-trimester pregnant women selected using purposive sampling. Participants were equally assigned into an Endorphin Massage group (n = 20) and a Kinesio Taping group (n = 20). Pain intensity was assessed before and after intervention using the Numeric Rating Scale (NRS), and data were analyzed using the Wilcoxon Signed-Rank Test and Mann–Whitney U Test. Both interventions significantly reduced low back pain intensity (p < 0.001), while comparative analysis showed that Endorphin Massage was significantly more effective than Kinesio Taping (Mean Rank = 30.50 vs. 10.50; p < 0.001). These findings indicate that although both interventions are effective, Endorphin Massage provides greater pain reduction and may be recommended as a first-line non-pharmacological approach for managing pregnancy-related low back pain in maternal healthcare practice.